Evolution of Telepathology: A Comprehensive Analysis of Global Telepathology Literature Between 1986 and 2017 - Engin ŞENEL; Yılmaz BAŞ (Federation of Turkish Pathology Societies, 2020)
Objective: Telepathology is an application of telemedicine providing remote evaluation and consultation of digital pathology images and can be used for educational or experimental purposes. Bibliometrics is a statistical discipline investigating publication patterns and trends in a certain academic field. Although bibliometric and scientometric studies are becoming increasingly popular, the relevant literature contains only one limited article related to telepathology. The aim of our study was to perform a holistic bibliometric analysis of the telepathology literature. Material and Method: Since the first article on telepathology was published in 1986, we included all indexed articles retrieved from Web of Science databases between 1986 and 2017. Results: We found that the USA covering 43.01% of all literature was the leading country in the telepathology field and was followed by Germany, Italy and the UK (n=120, 90 and 83, respectively). The countries with the most contributions were located in the continents of Europe and North America. The most productive source titles were Human Pathology, Journal of Telemedicine and Telecare, and Modern Pathology. Harvard University ranked first with 59 articles. The most commonly used keywords of the telepathology literature were "telepathology", "telemedicine", "digital pathology", "virtual microscopy" and "telecytology". We noted that all of the ten countries with the most contributions were in the developed category of UN classification and all twenty of the most productive institutions were from developed countries. Conclusion: We suggest that researchers from developing and least developed countries should be encouraged to carry out novel studies since telemedicine is a required and promising technology for rural developing or least developed areas in which access to health care is difficult.